CORPORATE GOVERNANCE AS AN EFFECTIVE INSTRUMENT FOR INDIAN LEADERSHIP - Pathak, Neeraj; Kumar, Sunil (International Journal of Psychosocial Rehabilitation, 2020)
This paper aims to provide a good governance system in India by describing its fundamental features and shortcomings and highlights the need for creative approaches. When interpreted in the sense of its time, no theory of governance could be intelligible. India’s 60-year democracy has clearly demonstrated that good governance needs to be geared towards improving social opportunities and reducing poverty. According to the paper, good governance means ensuring liberty, democracy, education and the efficient delivery of services. The document discusses these issues in depth and analyzes administrative and political defects. This describes crime and corruption as two primary problems. In particular, the study highlight shifts in the context and content of national freedom movement principles in relation to, and effect on, the smooth management and intellectual build-up of the institutions of the Indian State. This paper discusses many areas of concern which should be aggressively addressed and calls for cooperation between policy actions, the market and civil society. Typically speaking, inventions occur. However, there are two fields in which developments require special attention, namely women’s economic empowerment and livelihood initiatives focused on local capital and developed skills. The maintenance of democratic values in a multi-ethnic society remains a challenge. That is because the incorporation in a single political system of several ethnic groups means that the fundamental problem of ethnic conflict also comes together.